Patient Engagement in Neurological Clinical Trials Design: A Conference Summary. Issue 6 (17th June 2015) - Cobb, Enesha M.; Meurer, William; Harney, Deneil; Silbergleit, Robert; Lake, Bray Patrick; Clark, Christina; Gipson, Debbie; Barsan, William
Abstract: Objectives: The conference objectives included educating patients and advocates about clinical trials, educating the clinical research community about patient perspectives on participating in clinical trial design, and identifying strategies to increase participation in clinical trial design for neurological disorders. Design: Observations were noted during a 1‐day conference attended by patients, patient advocates, clinical trial staff, and investigators. The conference offered didactic sessions, small, and large group discussions. Participants: Conference participants were patients, patient advocates, clinical trial staff, students, and investigators interested in engaging patients in clinical trial design for neurological disorders. Measures: Conference participants were asked to consider lessons learned that could increase patient engagement in clinical trial design. Results: We found that there is growing interest in including patients in the design of clinical trials for neurological disorders. Several themes emerged on how to move forward: networking; the multifaceted roles of advocates in research; training and education; creating patient–researcher partnerships; and clinical trials regulation issues. Conclusions: The conference provided a forum for dialogue regarding stakeholder engagement in the design of clinical trials for neurological disorders. This experience provides a template for replication and dissemination of this conference and informs next steps to accelerate the pathway from dialogue to action.